3D finite element model based on CT images of tooth - Germana De Villa Camargos; Priscilla Cardoso Lazari-Carvalho; Marco Aurélio de Carvalho; Mariane Boaventura Castro; Naysa Wink Neris; Altair Antoninha Del Bel Cury (Universidade Estadual de Campinas, 2020)
Aim: This study aimed the description of a protocol to acquire a 3D finite element (FE) model of a human maxillary central incisor tooth restored with ceramic crowns with enhanced geometric detail through an easy-to-use and low-cost concept and validate it through finite element analysis (FEA). Methods: A human maxillary central incisor was digitalized using a Cone Beam Computer Tomography (CBCT) scanner. The resulted tooth CBCT DICOM files were imported into a free medical imaging software (Invesalius) for 3D surface/geometric reconstruction in stereolithographic file format (STL). The STL file was exported to a computer-aided-design (CAD) software (SolidWorks), converted into a 3D solid model and edited to simulate different materials for full crown restorations. The obtained model was exported into a FEA software to evaluate the influence of different core materials (zirconia - Zr, lithium disilicate - Ds or palladium/silver - Ps) on the mechanical behavior of the restorations under a 100 N applied to the palatal surface at 135 degrees to the long axis of the tooth, followed by a load of 25.5 N perpendicular to the incisal edge of the crown. The quantitative and qualitative analysis of maximum principal stress (ceramic veneer) and maximum principal strain (core) were obtained. Results: The Zr model presented lower stress and strain concentration in the ceramic veneer and core than Ds and Ps models. For all models, the stresses were concentrated in the external surface of the veneering ceramic and strains in the internal surface of core, both near to the loading area. Conclusion: The described procedure is a quick, inexpensive and feasible protocol to obtain a highly detailed 3D FE model, and thus could be considered for future 3D FE analysis. The results of numerical simulation confirm that stiffer core materials result in a reduced stress concentration in ceramic veneer.